2021
DOI: 10.1159/000515899
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Long-Term Trends in Length of Hospital Stay, Postmenstrual Age at Discharge, and Survival in Very Low Birth Weight Infants

Abstract: <b><i>Introduction:</i></b> In very low birth weight (&#x3c;1,500 g, VLBW) infants, morbidity and mortality have decreased substantially during the past decades, and both are known to be lower in girls than in boys. In this study, we assessed sex-specific changes over time in length of hospital stay (LOHS) and postmenstrual age at discharge (PAD), in addition to survival in VLBW infants. <b><i>Methods:</i></b> This is a single-center retrospective cohort anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Male sex has previously been identified as a risk factor for longer hospital stay, higher postmenstrual age at discharge and lower survival. 31 In addition, we previously reported that males had significantly longer cumulative MV compared with females. 32 Our study has limitations.…”
Section: Discussionmentioning
confidence: 90%
“…Male sex has previously been identified as a risk factor for longer hospital stay, higher postmenstrual age at discharge and lower survival. 31 In addition, we previously reported that males had significantly longer cumulative MV compared with females. 32 Our study has limitations.…”
Section: Discussionmentioning
confidence: 90%
“…The mean LOS of male newborns was significantly longer than that of females (P < 0.002), which was consistent with a previous report. 9 In addition, the death rate of males was higher than females. 9 A previous study reported that the global CD rates have continuously increased from 1990 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, the death rate of males was higher than females. 9 A previous study reported that the global CD rates have continuously increased from 1990 to 2018. 14 China has one of the highest CD rates in the world.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations